How Redundant Are Redundant Color Adjectives? An Efficiency-Based Analysis of Color Overspecification - Rubio-Fernández, Paula (Frontiers in Psychology, 2016)
Color adjectives tend to be used redundantly in referential communication. I propose that redundant color adjectives are often intended to exploit a color contrast in the visual context and hence facilitate object identification, despite not being necessary to establish unique reference. Two language-production experiments investigated two types of factors that may affect the use of redundant color adjectives: factors related to the efficiency of color in the visual context and factors related to the semantic category of the noun. The results of Experiment 1 confirmed that people produce redundant color adjectives when color may facilitate object recognition; e.g., they do so more often in polychrome displays than in monochrome displays, and more often in English (pre-nominal position) than in Spanish (post-nominal position). Redundant color adjectives are also used when color is a central property of the object category; e.g., people referred to the color of clothes more often than to the color of geometrical figures (Experiment 1), and they overspecified atypical colors more often than variable and stereotypical colors (Experiment 2). These results are relevant for pragmatic models of referential communication based on Gricean pragmatics and informativeness. An alternative analysis is proposed, which focuses on the efficiency and pertinence of color in a given referential situation.